The Influence Of Organizational Culture, Compensation, And Work Discipline On Employee Performance At Hospital. Satria Medika Bekasi - Eka Nur Azizah; Ibnu Haris Nasution (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2023)
The purpose of this research is to explain the influence of organizational culture, compensation and work discipline on the performance of hospital employees. Satria Medika Bekasi. This type of research is quantitative. The population in this study were hospital employees. Satria Medika Bekasi. Retrieval of data using saturated sampling which is distributed to 60 respondents. Data collection techniques in this study were questionnaires and documentation with Multiple Linear Regression Analysis, with the help of SPLS 4.0 software. The results of this study indicate that Organizational Culture, compensation and work discipline simultaneously have a significant effect on employee performance. The adjusted R-square value is 0.722, meaning the contribution of organizational culture, compensation and work discipline. Partially, organizational culture has no significant effect on employee performance, while compensation and work discipline have a significant effect on employee performance.